Economic viability of non-commercial and extensive rabbit breeding : a Slovenian case study - Prišenk, Jernej (Array, 2018)
The aim of this study is to present the calculation of technological and economic viability in rabbit meat production. The input data and due results were based on a real case (farm) from Slovenia. The farm primarily produces rabbit meat for self-sufficient consumption, not for commercial purposes. The economic calculations were based on data collected from two production cycles, totalling 221 rabbits. Results show that production is economically justified when the selling price of rabbit meat amounts to at least 8 EUR/kg. Should the selling price of rabbit meat reach 9 EUR/kg, the financial result would increase for approximately 15 %. The analysis of economic viability in rabbit meat production confirms that such production is economically justified.